Facile and low-cost mechanical techniques for the fabrication of solution-processed polymer and perovskite thin film transistors. (26th July 2018) - Habibi, Mehran; Eslamian, Morteza
Abstract: Low-temperature solution-processed polymer and perovskite thin film field effect transistors (FETs) are attractive, as they are compatible with flexible and printed electronics. Given that chemical treatment of the FET channel is expensive and tedious, and sometimes damages the underneath (dielectric) solution-processed layers, in this work, two facile and scalable mechanical treatment techniques are proposed. In the case of polymer FET, the wet spun film was excited by ultrasonic vibration imposed on the substrate. It is demonstrated that the micromixing effect induced by the ultrasonic radiation results in disentanglement, reorganization, and recrystallization of the polymer chains in the wet film. Ultrasonic vibration also improves the film leveling and uniformity and enhances the charge mobility of the channel of the polymer FET. In the case of the perovskite FET, we found that nitrogen blowing over the spun sample of the perovskite solution is a facile, yet effective substitution for the conventional anti-solvent treatment, commonly used to control the solvent evaporation rate. By nitrogen blowing, we achieved a uniform film of perovskite deposited on a solution-processed dielectric layer with domain sizes up to several hundreds of nanometers. By applying these techniques, the linear charge mobility of 0.041 cm 2 Vs −1 and 0.055 cm 2 Vs −1 were obtained for polymer and perovskite FETs under illumination, respectively. It is shown that while the performance of the polymer FET is only slightly sensitive to illumination, the perovskite FET performs well only under illumination.